Quelles relations sont envisageables entre la quatrième année de formation et la recherche à l’École nationale supérieure du paysage (ENSP) ? - Pascal Aubry (Projets de Paysage)
The article aims to enrich the debate, and overcome the inertia that could face the research in the ENSP in Versailles. More precisely, it proposes to identify the possible articulations between the research on landscape and the fourth year of the DPLG landscape studies. In a first part, the issue is analyzed in its context and the fundamental exercises are defined : TPFE and APR as well as the courses taught during the final study year in this landscape project school. Based on documents enlightening this articulation Research/DPLG 4, two types of research are identified. One considers the TPFE and the APR as the objet and the starting point of the research ; the other one, more timid, reckons that TPFE and APR could constitute, by themselves, a form of research. This contribution allows to point out the obstacles and the solutions related to the development of a research, from the professionalizing year in the ENSP landscape studies.